MEDIALINGUISTICS AS A MODERN SCIENTIFIC DIRECTION - Vokhidova, Tamanno (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
The features of media linguistics as a current scientific direction are considered. A distinction is made between the concepts of mass communication and the media. The identified features of the syntactic organization of the interview are determined by the desire to save language resources, which is predetermined, in particular, by the dialogical nature of the type of text under consideration. The term “media linguistics” itself contains two basic components in its structure – media (mass media) and linguistics. The object of study of the new discipline was a semiotically complicated text. The subject, in turn, is the study of the functioning of languages in the field of mass communication, and the text is characterized as a media text. Based on this, it becomes obvious that media linguistics is engaged in a comprehensive study of a certain area of speech use - the language of the media.